Foundations and applications of engineering mechanics - Ram, H. D.; Chauhan, A. K. (New Delhi Cambridge, 2016)
"Provides a comprehensive discussion of the fundamental theories and principles of engineering mechanics"--
Keywords: Mechanics, Applied